Characterization and functional properties of some natural Acacia gums - Daoub, Rabeea M.A.; Elmubarak, Aarif H.; Misran, Misni; Hassan, Elfatih A.; Osman, Mohammed E. (Elsevier, 2018)
Authentic representative gum exudate samples from Acacia species namely Acacia senegal var. senegal (ASG), Acacia mellifera (AMF), Acacia seyal var. seyal (ASY), and Acacia tortilis var. raddiana (ATR), were physicochemically analyzed. The moisture, ash, nitrogen and protein content, pH, specific optical rotation, and number average molecular weight were found to be ranging from 9.76% to 8.35%, 3.40% to 2.05%, 0.243% to 1.549%, 1.610% to 10.378%, 4.45 to 4.94, −48.25 to +86.75 and 0.24 × 106 to 2.95 × 106 respectively. The 13C and 1H NMR spectra of gum samples showed similarity in individual sugar components, but characteristic patterns of each gum, were observed. FTIR spectra of the studied gums show the presence of the same functional groups in the four gums. DSC and TGA thermograms were characteristic for each gum. Evaluation of the functional properties of the four gums indicated that ATR gum bears the best emulsification characteristics in terms of emulsion's stability and emulsification power.